Estudio de la innovación de procesos en la pequeña y mediana industria en el sector manufacturero de la ciudad de Latacunga. - Medina Romero, Catheryn Mariela Molina Panchi, Alex Andrés (2019)
This research project focuses on the study of the innovation process in the micro, small and medium scale industries in the manufacturing in Latacunga sector. In this sense, this thesis aims to achieve innovation in the processes in micro, small and medium industries. Through the socalled Oslo Manual, it was applied an information survey that helped to measure the innovation process in terms of: research to develop new processes, implementation of reengineering activities, staff training for business process improvement, incorporation of tools, machines or equipment, software incorporation, acquisition of goods linked to the process improvement, procurement of technical assistance or scientific services, incorporation of new technologies such as the use of patents, trademarks, designs; application of marketing methods, and innovation of new or significantly improved processes, proving in this sense that 80% of the micro, small and medium scale industries of Latacunga. Has not executed innovation processes. Each activity proposed for the innovation processes of industries in Latacunga is to be met through the participation of student working groups of the Industrial Engineering Career, since it is intended to provide technical support to the micro, small and medium scale industries of the manufacturing sector of the city through Training Projects, Generative Projects, Degree Projects, Integrating Projects and Pre-Professional Practices. Thus, the students will contribute to the industries by transmitting and imparting knowledge obtained in their academic training, consequently each of the participating industries will improve their processes and increase their production. This innovation process will generate confidence in consumers and contribute to the development of Latacunga and the province of Cotopaxi.